HUBUNGAN ANTARA PENGETAHUAN DENGAN PERILAKU PASIEN PENGGUNA VITAMIN DI PUSKESMAS TOULUAAN DAN PUSKESMAS POSUMAEN - Cindy R. Rotulung; Gayatri Citraningtyas; Imam Jayanto (UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTThere were still errors in the used of vitamins.Â While as was known vitamins were not products that were completely safe for everyone.Â Liked drugs, vitamins with active ingredients provided pharmacological effects that could also caused side effects in susceptible individuals, so more warning about side effects and potential interactions was needed to avoided serious health problems. The aim of this study was to analyze the correlation between knowledge and patients behavior who consume vitamins at the Touluaan Health Center and Posumaen Health Center. The type of the study was a descriptive analytic research with a cross-sectional design, totaling as many as 100 samples including all outpatients who received vitamin prescriptions at non-inpatient health centers in Southeast Minahasa Regency, including 58 patients at the Touluaan Health Center and 42 patients at the Posumaen Health Center. Questionnaires and interviews were employed to collect data, which was then analyzed using a computerized statistical program with the Spearman test. The results of this study showed that the level of knowledge of the respondent's vitamin medicinal product was 48% in a good category, 49% in enough category, and 3% in a less category. Furthermore, at the behavior level of respondents using vitamin medicinal products were 58% in a good category, 37% in enough category, and 5% in a less category. The Spearman test resulted in a significant value of 0.016, a correlation coefficient of 0.240, and a positive (+) correlation direction. The conclusion indicated that there was no correlation between knowledge and the use of vitamins in outpatients at the Touluaan Health Center and Posumaen Health Center.Keywords: Knowledge, Behavior, Patient, Vitamins, Health Center.ABSTRAKMasih didapatkan kesalahan dalam penggunaan vitamin. Sedangkan seperti yang diketahui vitamin bukanlah produk yang benar-benar aman untuk semua orang. Seperti obat, vitamin dengan bahan aktif memberikan efek farmakologi yang juga dapat menyebabkan efek samping pada individu yang rentan, sehingga perlu peringatan lebih akan efek samping dan potensi interaksi untuk menghindari masalah kesehatan yang serius. Tujuan dari penelitian ini adalah untuk melihat hubungan antara pengetahuan dengan perilaku pasien pengguna vitamin di Puskesmas Touluaan dan Puskesmas Posumaen. Jenis penelitian ini adalah deskriptif analitik, menggunakan desain cross sectional, sebanyak 100 sampel dalam penelitian ini adalah semua pasien rawat jalan yang menerima resep vitamin di Puskesmas non rawat inap Kabupaten Minahasa Tenggara, 58 orang di Puskesmas Touluaan, 42 orang di Puskesmas Touluaan. Data dikumpulkan melalui kuesioner dan wawancara, analisa data dilakukan menggunakan program statistik komputerisasi dengan uji Spearman. Hasil penelitian ini menunjukkan bahwa tingkat pengetahuan produk obat vitamin responden yaitu kategori baik 48%, cukup 49% dan kurang 3%. Pada tingkat perilaku penggunaan produk obat vitamin responden yaitu kategori baik 58%, cukup 37% dan kurang 5%. Hasil uji spearman didapatkan nilai signifikan 0,016, nilai koefisien korelasi sebesar 0,240, dan arah korelasi yaitu positif (+). Kesimpulannya yaitu tidak adanya hubungan yang bermakna antara pengetahuan dan penggunaan vitaminÂ pada pasien rawat jalan di Puskesmas Touluaan dan Puskesmas Posumaen.Kata Kunci : Pengetahuan, Perilaku, Pasien, Vitamin, Puskesmas.